Understanding air-conditioned lives: qualitative insights from Doha. Issue 1 (16th February 2022) - Hitchings, Russell
This paper uses an interview study in Doha, the capital city of Qatar, to consider the role of qualitative methods in identifying how human relationships with air-conditioning are influenced. Drawing on discussions with three groups of comparatively affluent residents who spent significant amounts of time in air-conditioned spaces, it makes four points to researchers hoping to encourage less energy demanding lifestyles. The first is that 'comfort is only one aspect' when a premature focus on comfort obscures other potentially important analytical concerns. The second is that 'air-conditioning changes cultures' when valuable insights may be gleaned from what people say about how it creates, rather than responds to, local preferences and expectations. The third is that 'comparison can be instructive' when different groups may feel themselves to possess very different relationships with air-conditioning. The fourth is that 'discussion can disappear' when those hoping to influence these relationships may benefit from understanding when and how 'conditioning conversations' currently occur and how they could be part of processes of positive local change. After substantiating these points, wider conclusions are drawn about the promotion of less energy consumptive ways of adapting to a warming world and the value of this approach to the cultural geography of air-conditioning. Practice relevance: Strategies for influencing human relationships with air-conditioning stand to benefit from an appreciation of how this technology has become part of everyday life in particular places. Drawing on an interview study in Doha, this paper argues that qualitative research methods can illuminate these processes in original ways and provide fresh ideas about how life with air-conditioning is influenced. With respect to the Doha case, the paper concludes that a fuller public conversation about air-conditioning levels could spark a process of local change with the potential to result in reduced energy consumption.